Detection of sonic hedgehog in patients undergoing orthognathic surgery. (2016) - Kunisada, Yuki; Shimo, Tsuyoshi; Masui, Masanori; Yoshioka, Norie; Ibaragi, Soichiro; Matsumoto, Kenichi; Okui, Tatsuo; Kurio, Naito; Domae, Shohei; Kishimoto, Koji; Nishiyama, Akiyoshi; Sasaki, Akira
Highlights: Mandibular osteotomy healing is a unique process that leads to bone regeneration. Several growth factors are known to be involved in the critical initial stage of fracture healing. Local concentrations of certain factors after the mandibular osteotomy are not well understood. Sonic Hedgehog (SHH) is a regulatory protein involved in bone fracture healing. We evaluated the local levels of SHH expression after mandibular osteotomy. Abstract: Purpose: Sonic Hedgehog (SHH) is a regulatory protein involved in bone fracture healing. Orthognathic surgery involves surgical osteotomy of the mandible or maxilla to restore the proper anatomic and functional position in patients with dentofacial deformity. The purpose of this study was to analyze SHH local blood serum concentrations after osteotomy to gain further understanding of the molecular regulation of the initial stage of osteotomy healing. Methods: Serum samples (local drainage and peripheral venous) of 34 patients (24 females and 10 males, mean age was 23.4 (16–42) years) who underwent orthognathic surgery were isolated from patients at different time points during the perioperative period. The levels of SHH, soluble receptor activator of nuclear factor-κB ligand (sRANKL) and osteoprotegerin (OPG) were measured using ELISA. Results: SHH was detected in the local drainage immediately after osteotomy (309.5 ± 58.2 pg/ml), and decreased for 2 days after the operation (197.5 ± 43.6 pg/ml). The sRANKL local serum concentrations were at the maximum level immediately after the operation (141.4 ± 22.6 pg/ml) and decreased for 2 days (110.1 ± 23.4 pg/ml). On the other hand, the OPG concentration in the local serum was at a minimum after osteotomy (59.4 ± 4.6 pg/ml) and reached its maximum (181.5 ± 17.8 pg/ml, P < 0.01) at 2 days after osteotomy. SHH and OPG local serum levels on day 2 were associated with the amount of bleeding during the operation. The local drainage serum level of SHH of maxillary/mandibular osteotomy had a tendency to be higher than that of mandible-only osteotomy at 2 days after operation. Conclusions: Elevated levels of SHH in local serum after osteotomy, especially during the initial stage of healing, indicates its importance in osteotomy healing.